Exploring Business Process Management (BPM) Challenges in a Startup Environment - Witra, Widyasari Puspa Permata (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
The primary aim of the article is to discover Business Process Management (BPM) challenges when applied in a startup environment. This concept is an increasingly popular concept nowadays where BPM is one of mature disciplines that drives companies’ success. Whereas startup companies also becoming a trend as the Information Technology (IT) is developed and they have different organizational values compared to most companies in general. A Systematic Literature Review (SLR) is performed to offer an impactful and insightful literature concerning BPM in startup environment. The papers used in this article are from the most honored journal publishers such as Elsevier, Emerald Insight, Springer, Taylor and Francis, Wiley,  and Sage Publications. A total of 3332 articles are picked based on the keyword. Then, 22 articles are picked according to the content of the article. Results show that there are 11 out of 30 BPM capability areas may be facing some challenges when applied in a startup environment. Therefore those 11 BPM capability areas need some improvement in order to be suitable for startup environment. Fortunately, the remaining are just good as is because they are compatible with startup environment.